Regulatory Capacity Review of Kenya - International Finance Corporation; Multilateral Investment Guarantee Agency; World Bank (Washington, DC, 2017)
Regulatory reform has emerged as an important policy area in developing countries. For reforms to be beneficial, regulatory regimes need to be transparent, coherent, and comprehensive. They must establish appropriate institutional frameworks and liberalized business regulations; enforce competition policy and law; and open external and internal markets to trade and investment. This report examines the institutional set-up for and use of regulatory policy instruments in Kenya. It is one of five reports prepared on countries in East and Southern Africa (the others are on Zambia, Uganda, Rwanda, and Tanzania). The report is based on a review of public documents prepared by the government, donors, and the private sector, and on a limited number of interviews with key institutions and individuals.